PT. TELEKOMUNIKASI SHARE PRICE PREDICTION ANALYSIS INDONESIA USING THE TRIPLE METHOD EXPONENTIAL - Khairawati, Khairawati; Fuadi, Wahyu; Fariadi, Dedi (CV. Radja Publika, 2022)
The capital market is one of the investment models that is currently growing so rapidly. The amount of interest in investing makes many people who experience losses, due to not understanding the investment risks. This requires technical analysis skills. In this research, we will analyze the prediction of PT. Telekomunikasi Indonesia (TLKM) from 2021 to 2022. The variables used in this study are historical prices ranging from Open, High, Low, and Close prices. The stages used are 184 historical data collection, where the data is taken through Google's financial database and yahoo Finance. Then the calculation process uses the Triple Exponential Smoothing method, the system accuracy process is calculated for the forecast error value using the Mean Absolute Percentage Error (MAPE).